2019
DOI: 10.5539/jas.v11n8p165
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Chili Pepper Genotypes (Capsicum spp.) Resistant to Meloidogyne enterolobii

Abstract: Chili pepper has economic importance and is the dominant Solanaceae in the market of spicy spices. Among the pathogens that affect this crop, Meloidogyne enterolobii is one of the most important because it presents a wide range of hosts and there are no resistance genes identified that are efficient against this species. The present study aimed to evaluate the reaction of chili pepper genotypes (Capsicum spp.) to M. enterolobii in order to identifify genetic resistance. Three experiments were conducted in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
6
1
Order By: Relevance
“…Two pepper genotypes were chosen (Capsicum spp.) based on previous studies (Marques et al, 2019), which presented resistance and susceptibility to M. enterolobii, with RF equal to 0.08 (C. chinense -UFGCCH 24 'Bode Roxa') and 7.21 (Capsicum baccatum -UFGCBA 3 'Cambuci'). UFGCCH stands for Universidade Federal de Goiás, Capsicum chinense genotype 24 and UFGCBA 3 stands for Universidade Federal de Goiás, Capsicum baccatum genotype 3…”
Section: Methodsmentioning
confidence: 91%
“…Two pepper genotypes were chosen (Capsicum spp.) based on previous studies (Marques et al, 2019), which presented resistance and susceptibility to M. enterolobii, with RF equal to 0.08 (C. chinense -UFGCCH 24 'Bode Roxa') and 7.21 (Capsicum baccatum -UFGCBA 3 'Cambuci'). UFGCCH stands for Universidade Federal de Goiás, Capsicum chinense genotype 24 and UFGCBA 3 stands for Universidade Federal de Goiás, Capsicum baccatum genotype 3…”
Section: Methodsmentioning
confidence: 91%
“…Another species that has gained importance recently is M. enterolobii for which, the sources of resistance against the major species of Meloidogyne are ineffective on its control [273]. Two genotypes, named UFGFR 05 (C. frutescens) and UFGCH 24 (C. chinense) are recently identified as resistant to M. enterolobii [269].…”
Section: Root-knot Nematodesmentioning
confidence: 99%
“…Table 2 shows differences between susceptible and resistant genotypes regarding RF and the Pf of the nematodes in the roots. According to the criterion of Oostenbrink (1966), it is considered a resistant plant with RF <1 and susceptible with RF >1.0, an expected result since these genotypes have been previously evaluated (Marques et al, 2019). However, there were no differences between the nematode density (number of nematodes per 10 g of roots), demonstrating that in both Capsicum spp.…”
Section: Discussionmentioning
confidence: 99%
“…After previous studies that found Capsicum spp. genotypes resistant to M. enterolobii (Marques et al, 2019) it is important to identify the mechanisms involved in the resistance, which may be related to the plant's biochemical defence. Therefore, the objective of this study was to compare the biochemical defence response of two chilli pepper ( Capsicum spp.)…”
Section: Introductionmentioning
confidence: 99%